From sustainable development to resilience? (Dis)continuities in climate and development policy governance discourse. (12th August 2022) - Ferguson, Peter; Wollersheim, Linda
Abstract: 'Resilience' has become a central, albeit ambiguous, concept in environmental and development governance discourse since the mid‐2000s. However, whether this constitutes merely the updating of the language of sustainable development or a new discourse of environmental and development governance is unclear. Resilience is often characterised as a form of neoliberal governmentality that seeks to individualise the mitigation of ecological risks, implying that it is simply an extension of neoliberal sustainable development . However, this elides other possible articulations of resilience within environmental and development governance discourse more broadly. By developing and applying an innovative discourse analysis method, this article clarifies the relationship between sustainable development and resilience across these wider fields. We find that resilience is also articulated as a response to the failure of neoliberal sustainable development ; as an integrating discourse of climate security and sustainable development; as a prerequisite for sustainable development; and as qualitatively different to sustainable development .